Adaptive compensation of nonlinear time varying torque disturbance in rigid robots - Astolfi,A (1994)
This paper presents a new approach to the control of rigid robots when actuator dynamics and nonlinearities (e.g. saturation), Coulumb friction, ... are relevant. An adaptive like algorithm is used in order to obtain desired trajectory tracking in the presence of unknown, non linear, time varying torque disturbances acting on the robot.